A Comparative Study between Co‐ and CoFe2O4‐NPs Catalytic Activities in Synthesis of Flavone Derivatives; Study of Their Interactions with Estrogen Receptor by Molecular Docking. Issue 23 (19th June 2018) - Hajipour, Abdol R.; Khorsandi, Zahra; Fakhari, Farzaneh; Mortazavi, Maryam; Farrokhpour, Hossein
Abstract: Flavonols are polyphenolic compounds with diverse pharmacological and biological activities. In this work, a general method for large‐scale synthesis of these biologically important compounds, using available substrates, is reported. The reaction was occurred via Michael‐dehydrogenative reaction using green, inexpensive and highly efficient heterogeneous cobalt catalysts without any ligands and/or additives, the activity of CoFe2 O4 and Co‐NPs was studied and compared. These procedures have advantages such as lack of hazardous oxidants, simplicity of work‐up, eco‐friendly of reaction medium, mild reaction conditions and high yield of products. In addition, the binding modes of synthesized compounds to estrogen receptor (ER) was studied by molecular docking and good results was obtained. Abstract : A general way for large‐scale synthesis of flavone derivatives as biologically important compounds is reported using green, inexpensive and highly efficient heterogeneous cobalt catalysts without any ligands and/or additives, the activity of CoFe2 O4 and Co‐NPs was studied and compared.